Identification of B-cell Epitope of Leishmania donovani and its application in diagnosis of visceral leishmaniasis. Issue 16 (10th December 2017) - Jamal, Fauzia; Dikhit, Manas Ranjan; Singh, Manish K.; Shivam, Pushkar; Kumari, Sarita; Pushpanjali, Sinha; Dubey, Amit K.; Kumar, Prakash; Narayan, Shyam; Gupta, Anil K.; Pandey, Krishna; Das, V.N.R.; et al.
Abstract : Diagnosis of visceral leishmaniasis (VL) is often hindered by cross-reactions with antigens from other related parasite infections. This study aimed to develop an immunochromatographic test (ICT) which can detect the antigen present in circulating immune complexes (CICs) of VL patients using B-cell epitope-specific antibodies. MS analysis of six immunoreactive 2DE spots revealed two epitopes i.e. RFFVQGDGIGQHSLQEALERR (P1 ) and RRVAVLVLLDRL (P2 ) (From a hypothetical protein [Acc No: XP_003861458.1]). The epitope conservancy analysis suggested that the linear epitope (P1 P2 ) is 97–100% conserved among Leishmania species and diverged from Homo sapiens (61% query coverage and 80% identity). Further, immunoinformatics analysis of hydrophilicity and flexibility confirmed the antigenicity of the peptide fragment. The linear epitope (P1 P2 ) was synthesized (98% purity) and the purity was confirmed by high-performance liquid chromatography and MS. The indirect Enzyme linked immunosorbent assay results confirmed the presence of the corresponding antibody in VL patient's sera but not in those of healthy and other diseases. The result demonstrated a sensitivity 90%; Se Cl95% (82.16–96.27)% and specificity 100%; Sp Cl95% (84.56–100)% which indicated the possibility to be used as a diagnostic tool. Sensitivity, specificity, and diagnostic efficiency of colloidal gold conjugated anti-P1 P2 antibody ICT strip was 100, 95.2, and 96.7%, respectively, which is slightly better as compared to other ICT for VL. Though, our result indicated the utility of anti-P1 P2 antibody to detect CICs epitopes, a large-scale inspection in endemic and non-endemic area and in different ethnic population is needed for its validation and authentication.